2009
DOI: 10.1124/jpet.109.156620
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Administration Accelerates Progression of the Cell Cycle during Rat Liver Regeneration Induced by One-Third Hepatectomy

Abstract: We have shown that adenosine administration is capable of reversing fibrosis in the carbon tetrachloride-induced rat cirrhotic liver, stimulating the diminished proliferative potential of the cirrhotic liver. To characterize adenosine actions on liver cellular proliferation, we used rats subjected to one-third partial hepatectomy (PH). In PH animals acutely administered with adenosine (25-200 mg/kg b.w.), parameters indicative of cell proliferation were determined. In addition, hepatocyte growth factor (HGF), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Concerning the second model, PHx, we could show by an in silico approach that the differential gene expression induced by PHx is also characterized by an overrepresentation of TFBS for the same TFs—ETF, E2F, and SP‐1—indicating that such cytokine‐independent events contribute to the initiation of proliferation under conditions where the integrity of parenchyma remains intact. Recent work34 showing that nuclear E2F1 increases in rat hepatocytes after one‐third PHx corroborates the importance of this TF, independent of the species studied.…”
Section: Discussionmentioning
confidence: 53%
“…Concerning the second model, PHx, we could show by an in silico approach that the differential gene expression induced by PHx is also characterized by an overrepresentation of TFBS for the same TFs—ETF, E2F, and SP‐1—indicating that such cytokine‐independent events contribute to the initiation of proliferation under conditions where the integrity of parenchyma remains intact. Recent work34 showing that nuclear E2F1 increases in rat hepatocytes after one‐third PHx corroborates the importance of this TF, independent of the species studied.…”
Section: Discussionmentioning
confidence: 53%
“…In initial experiments, we analyzed expression of PCNA, a nuclear protein that is up-regulated in proliferating cells (Mendieta-Condado et al , 2009). In wild type mice acetaminophen caused in a time dependent increase in PCNA staining in hepatocyte nuclei in periportal regions of the liver, which was evident within 3 h and remained elevated for at least 96 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, in this study we found that the overexpression of the A2a receptor protein during cirrhosis decreases in the presence of IFC-305 (Figure 7), suggesting a role of this receptor in the described effect. Previously, we showed that the inhibitory effect of IFC305 in hepatic stellate cells activation was not mediated by adenosine receptors, but it was related with adenosine transport and intracellular AMP formation [42], neither in the adenosine acceleration of the cell cycle after one-third hepatectomy [19]. Possibly, a diminution of A2a receptor expression induced by the IFC305 increases adenosine transport into the cell promoting their effects in DNA repair and maintaining the energetic equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…In preestablished cirrhosis, adenosine increases collagen degradation, prevents its accumulation, preserves the energy and functional states of the liver, increases DNA synthesis, the mitotic index, and the expression of proliferating cell nuclear antigen (PCNA) [7]. Recently, we have demonstrated that adenosine administration accelerates progression of the cell cycle during liver regeneration in rats subjected to one-third hepatectomy [19]. Some of these effects, such as prevention of collagen accumulation and increase in DNA synthesis, have been reproduced with the IFC-305 [5, 10].…”
Section: Introductionmentioning
confidence: 99%